A Practical Method for Chairside Repair of Debonded Porcelain Denture Teeth - Mutlu ¨Ozcan, DMD, PhD (Journal of Prosthodontics, 2006)
The bonding of porcelain denture teeth to polymethylmethacrylate remains a clinical problem